Perinatal risk factors for neurocognitive impairments in preschool children born very preterm. - Potharst, Eva S; van Wassenaer-Leemhuis, Aleid G; Houtzager, Bregje A; Livesey, David; Kok, Joke H; Last, Bob F; Oosterlaan, Jaap (Developmental Medicine & Child Neurology, 2013)
AIM: This study aimed to compare a broad array of neurocognitive functions (processing speed, aspects of attention, executive functioning, visual-motor coordination, and both face and emotion recognition) in very preterm and term-born children and to identify perinatal risk factors for neurocognitive dysfunctions. METHOD: Children who were born very preterm (n=102; 46 males, 56 females), defined as a gestational age of less than 30 weeks and/or birthweight under 1000 g, and a comparison group of term-born children (n=95; 40 males, 55 females) were assessed at age 5 with the Wechsler Preschool and Primary Scale of Intelligence, Stop Signal Task, several tasks of the Amsterdam Neuropsychological Tasks, and a Digit Span task. RESULTS: When sociodemographic characteristics were taken into account, very preterm children scored worse than term-born children on all neurocognitive functions, except on tasks measuring inhibition and sustained attention, for which results were inconclusive. Effect sizes for group effects were small to medium (r(2) varying between 0.02 and 0.07). Principal component isolated four factors: visual-motor coordination, face/emotion recognition, reaction time/attention, and accuracy/attention. When sociodemographic and child characteristics at birth were accounted for, bronchopulmonary dysplasia was significantly negatively associated with all four components and also with working memory. INTERPRETATION: Very preterm children are at risk for problems on a broad array of neurocognitive functions. Bronchopulmonary dysplasia is an independent risk factor for impaired neurocognitive functioning.